Pelvic floor exercises to improve low back pain and activities of daily living for the elderly - Fera Gusmi Nurba; Muhammad Nurhadi Rahman; Dicky Moch Rizal (Physical Therapy Journal of Indonesia, 2025)
Background: Lower back pain is a prevalent health concern on a global scale, particularly among female and elderly demographics. The objective of this study was to assess the impact of regular pelvic floor exercises on the severity of low back pain and the enhancement of daily functioning in postmenopausal women. Methods: The present study employs a quasi-experimental design, incorporating a pre-post-test approach and a control group. Based on the extant data, 18 postmenopausal women will be distributed between the control group and the intervention group. The control group will participate in pelvic floor exercises thrice weekly for three weeks, while the intervention group will engage in pelvic floor exercises daily for three consecutive weeks. The collected data will be subjected to a paired sample t-test to make a pre-and post-intervention comparison, while an independent t-test will be employed to compare the groups at a significant level of p<0.05. Results: The average numeric rating scale (NRS) and modified Oswestry low back pain disability index (MODI) values in the control group after performing pelvic floor exercises were recorded as (6.0±1.4) and (20.3±7.3), respectively, while in the intervention group, they were (2.6±1.7) and (9.44±7.9). These data show a significant difference with a p-value < 0.000 (p < 0.05). A comparison between the control and intervention groups after performing pelvic floor exercises with different frequencies also revealed significant differences, with p-values of 0.000 and 0.008 (p<0.05), respectively. However, a larger difference was observed in the intervention group performing pelvic floor exercises daily, showing a much higher delta compared to the group exercising three times a week, with NRS values of (4.4±0.5) and MODI values of (19.7±1.7). Conclusion: In postmenopausal women, the group that performed pelvic floor exercises daily exhibited a significant reduction in NRS and MODI values compared to the group that performed exercises three times a week.